Translating National Policy to Improve Environmental Conditions Impacting Public Health Through Community Planning (Springer International Publishing, 2018)
This first-of-its-kind volume traces rarely explored links between public policy, the state of the environment, and key issues in public health, with recommendations for addressing longstanding intractable problems. Experts across diverse professions use their wide knowledge and experience to discuss hunger and food sustainability, land use, chronic and communicable diseases, child mortality, and global water quality. Interventions described are varied as well, from green technology breakthroughs to regulatory accountability, innovative urban planning and community policing programs. Chapters build and expand on each other's themes inspiring deeper understanding and critical thinking that further prompts readers to develop practical solutions leading to improvements in planetary and population health outcomes. Included in the coverage: · The challenge of implementing macroeconomic policy in an increasingly microeconomic world · Green aid flows: trends and opportunities for developing countries · Planning healthy communities: abating preventable chronic diseases · Foundations of community health: planning access to public facilities · International changes in environmental conditions and their personal health consequences Translating National Policy to Improve Environmental Conditions Impacting Public Health is developed for educators, students, and policymakers to generate awareness and review options to help create change in their communities. Federal agencies such as the Department of Health and Human Services, the National Institutes of Health, the EPA, and Housing and Urban Development will also find it salient. .